1994
DOI: 10.1007/bf00027145
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem II in a mutant of Chlamydomonas reinhardtii lacking the 23 kDa psbP protein shows increased sensitivity to photoinhibition in the absence of chloride

Abstract: The psbP gene product, the so called 23 kDa extrinsic protein, is involved in water oxidation carried out by Photosystem II. However, the protein is not absolutely required for water oxidation. Here we have studied Photosystem II mediated electron transfer in a mutant of Chlamydomonas reinhardtii, the FUD 39 mutant, that lacks the psbP protein. When grown in dim light the Photosystem II content in thylakoid membranes of FUD 39 is approximately similar to that in the wild-type. The oxygen evolution is dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 29 publications
(39 reference statements)
3
25
0
Order By: Relevance
“…This is in line with the earlier finding that a mutant of Chlamydomonas (FUD 39), which lacks the extrinsic 23-kDa protein of PSII (PsbP; Ref. 43), shows chloride ion deficiency in PSII and is highly susceptible to photodamage (37,45).…”
Section: Absence Of the Psbj Polypeptide Results In A Defectivesupporting
confidence: 90%
“…This is in line with the earlier finding that a mutant of Chlamydomonas (FUD 39), which lacks the extrinsic 23-kDa protein of PSII (PsbP; Ref. 43), shows chloride ion deficiency in PSII and is highly susceptible to photodamage (37,45).…”
Section: Absence Of the Psbj Polypeptide Results In A Defectivesupporting
confidence: 90%
“…Both samples generated a similar amount of long-living cations, indicating that the primary charge separation from P680 to the primary quinone is-still intact after partial inhibition of the watersplitting activity. The loss ofwater-splitting activity is therefore due to an irreversible damage of the donor side in agreement with earlier results (6,7,(10)(11)(12)(13)(14).…”
Section: Methodssupporting
confidence: 80%
“…In case of a transient malfunction of the water-splitting reaction, P680+ has an extended lifetime during which it can degrade (4) or damage other PSII components, including carotenoids, chlorophylls (Chl), possibly Z, the manganese binding sites, and other amino acids of the PSII proteins (5)(6)(7)(8)(9)(10). One or several of these damages result in an irreversible inhibition of the electron transfer from Z to P680+ and hence in an irreversible loss of the water-splitting activity (6,7,(10)(11)(12)(13)(14). Despite many investigations it is still not clear which of the various damages actually causes this inhibition.…”
mentioning
confidence: 97%
“…In previous studies, a Chlamydomonas reinhardtii mutant lacking PsbP showed decreased oxygen-evolving activity (Mayfield et al, 1987), and an increased concentration of Cl 2 was required to restore oxygen evolution in isolated thylakoid membranes (Rova et al, 1994). However, the in vivo photosynthetic properties of the mutant cells were not well characterized in these studies.…”
mentioning
confidence: 87%